2015
DOI: 10.1016/j.worlddev.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to Dynamic Markets and Rural Territorial Development in Latin America

Abstract: Linkage to dynamic markets is a key factor in understanding why different rural territories in Latin America perform differently. This paper combines two conceptual frameworks (from the new economic geography and economic sociology) for an in-depth analysis of the mechanisms that operate in this linkage and to identify key factors that allow for inclusive economic development. This analysis considers three rural territories that exemplify market linkages frequently observed in Latin America, where, although hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 17 publications
0
20
0
9
Order By: Relevance
“…Berdegué, Bebbington, and Escobal (2015a) found that Tungurahua is one of a small minority of places in rural Latin America where both growth and equity have been simultaneously achieved. 1 This has been achieved through a dynamic linkage between "hard factors" of the new economic geography (location, access to public services, adjacency to the city) and "soft factors" of economic sociology (interfamily relations, trust, and reciprocity) (Escobal et al 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Berdegué, Bebbington, and Escobal (2015a) found that Tungurahua is one of a small minority of places in rural Latin America where both growth and equity have been simultaneously achieved. 1 This has been achieved through a dynamic linkage between "hard factors" of the new economic geography (location, access to public services, adjacency to the city) and "soft factors" of economic sociology (interfamily relations, trust, and reciprocity) (Escobal et al 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We expand on Bronfenbrenner’s () human ecological framework to explore links between the microscale (family), the mesoscale (community and regional), and the macroscale (national and global). We also incorporate the human capabilities framework (Sen ) with a community capitals approach (Flora and Flora ) to understand how flows occur across these scales in a process of rural territorial dynamics that supports both economic growth and social inclusion (Berdegué, Bebbington, and Escobal ; Escobal et al ; Ospina Peralta and Hollenstein ). The article gives specific attention to the links between individual and family development trajectories and community well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Однако стоит отметить, что содержание понятия «сельская местность» варьируется в зависимости от страны. Соответственно и меры для развития территорий различаются (Escobal, Favareto, Aguirre, Ponce, 2015). Таким образом, проблема классификации поселений и территорий в зависимости от ключевых факторов, а также оценка эффективности мер по развитию сельских территорий является актуальной не только для поселений России, но и для стран Европы.…”
Section: зарубежная практикаunclassified
“…It does so by following the territorial actors (see Berdegué, Bebbington, & Escobal, 2015;Escobal, Favareto, Aguirre, & Ponce, 2015) who individually or collectively through different network constellations seek to promote, alter, or capture specific investments or institutional changes in order to achieve specific individual or societal outcomes (Araujo, Ferreira, Lanjouw, & Ö zler, 2008;Mahoney & Thelen, 2011;Robinson, 2010). These territorial actors include traditional large-scale land owners as well as small-scale farmers and dairy cooperatives (many of which were established with support from international development cooperation in the wake of the 1990 peace agreement), merchants, public employees, and politicians.…”
Section: Introductionmentioning
confidence: 99%